1983
DOI: 10.1017/s0021859600033487
|View full text |Cite
|
Sign up to set email alerts
|

The digestion of untreated and formaldehyde-treated soya-bean and rapeseed meals by cattle fed a basal silage diet

Abstract: The effect of pretreating soya-bean and rapeseed meals with formaldehyde was studied. Soya-bean and rapeseed meals, both untreated and formaldehyde-treated, were fed to cattle receiving a basal diet of silage in a 4 x 4 latin square. Formaldehyde treatment of both meals significantly reduced apparent N digestibility. All four protein supplements increased the amounts of non-ammonia N and amino acid N entering the small intestine over those obtained when silage was fed alone. Formaldehyde treatment of the meals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

1983
1983
1997
1997

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 35 publications
1
18
1
Order By: Relevance
“…Digesta was not sampled in the sheep, but from theoretical considerations, rumen degradation values of dried grass (0f85; Coelho da Silva, Seeley, Thomson, Beever & Armstrong, 1972), barley (0-80;Agricultural Research Council, 1980) and fishmeal/barley (0f42-0 56) and soyabean meal/barley (0 47-070; Ling & Buttery, 1978) indicates that the HP diet would be expected to increase the proportion of dietary protein reaching the post-ruminal tract compared with the LP diet. Indeed the formaldehyde treatment of soyabean meal used in this study has been shown to decrease the 'in sacco' degradability of soyabean meal, albeit in cattle, from the untreated value of 0-90 to 040 (Rooke, Brookes & Armstrong, 1983), which would further enhance the difference in quantities of undegraded dietary protein reaching the abomasum, the major site of gastrin G cells (Bunnett, 1984). The lack of difference in gastrin responses between diets in the sheep experiment suggests either that, once modified by rumen fermentation, the protein content of the diets was not sufficiently different to produce dissimilar gastrin responses or that there is less of a reliance on protein and its products of digestion for stimulation of gastrin release than there is in non-ruminant species.…”
Section: Discussionmentioning
confidence: 81%
“…Digesta was not sampled in the sheep, but from theoretical considerations, rumen degradation values of dried grass (0f85; Coelho da Silva, Seeley, Thomson, Beever & Armstrong, 1972), barley (0-80;Agricultural Research Council, 1980) and fishmeal/barley (0f42-0 56) and soyabean meal/barley (0 47-070; Ling & Buttery, 1978) indicates that the HP diet would be expected to increase the proportion of dietary protein reaching the post-ruminal tract compared with the LP diet. Indeed the formaldehyde treatment of soyabean meal used in this study has been shown to decrease the 'in sacco' degradability of soyabean meal, albeit in cattle, from the untreated value of 0-90 to 040 (Rooke, Brookes & Armstrong, 1983), which would further enhance the difference in quantities of undegraded dietary protein reaching the abomasum, the major site of gastrin G cells (Bunnett, 1984). The lack of difference in gastrin responses between diets in the sheep experiment suggests either that, once modified by rumen fermentation, the protein content of the diets was not sufficiently different to produce dissimilar gastrin responses or that there is less of a reliance on protein and its products of digestion for stimulation of gastrin release than there is in non-ruminant species.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, supplementation with protein increased ammonia concentrations with both treated silages. Rooke et al (1983a) also found increased rumen ammonia levels when formic acid silage was supplemented with rapeseed meal. Molar proportions of acetate were significantly lower with enzyme-treated silage diets.…”
Section: Digestion Studymentioning
confidence: 77%
“…and N contents of the silage residues from the polyester bag incubations and rumen bacteria were determined according to Rooke, Brookes & Armstrong (1983). The silage residues from each pair of duplicate polyester bags were bulked prior to determination of their N and amino acid contents.…”
Section: Analytical Proceduresmentioning
confidence: 99%